Analisis Perbaikan Kualitas Pelayanan Menggunakan Metode Quality Function Deployment (Studi Kasus Cafe XYZ Rawalumbu) - Alloysius Vendhi Prasmoro; Chusnul Chotimah; Denny Siregar (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2020)
ABSTRACT Culinary business in Bekasi is growing more and more, both cafes or other fast food restaurants. This encourages entrepreneurs, investors to do culinary business. One of the fast food culinary businesses is the XYZ cafe. This study discusses the analysis of service quality in XYZ cafe about voice of customers to increase customer satisfaction at XYZ cafe. The purpose of this study is to determine the priority scale to increase the customers satisfaction based on the voice of customer and know what technical requirements should be given by cafe XYZ to does what customers need . The method used is the QFD, using the matrix house of quality. The results of this study are 15 Voice OF customer attributes that have also been sorted by priority scale of improvement, with the first priority being the taste of delicious and fresh and there are 8 attributes of technical requirements. Keywords: Service Quality, Voice of Customer, customer satisfaction, Quality Function Deployment (QFD), House of Quality